About the History of Design through teaching and innovation - Alberto Caruso (Agathón)
The aim of this article is to reflect on two different but complementary aspects of the work of the historian of industrial design: his role as a researcher on the one hand, and the one as a lecturer on the other. The marginalisation of history as part of the teaching offer for industrial design’s students can be attributed to the idea that the industrial designer is becoming a problem solver. This is in line with the technological progress that has characterised the field of industrial design over the last decades. This contribution intends to show that the employment of new technology for industrial design projects does not necessarily lead to the end of traditional professions. On the contrary, such a development could be the opportunity to challenge traditional lecturing methods and introduce the flipped classroom in the context of academic teaching.